NILAI EKONOMI DAN KONTRIBUSI HASIL HUTAN BUKAN KAYU TERHADAP PENDAPATAN MASYARAKAT (STUDI KASUS PADA DESA HALABAN KECAMATAN LAREH SAGO HALABAN, KABUPATEN 50 KOTA, SUMATERA BARAT) - Annisa Wahyu Safitri; rina NOVIA YANTI; Eno Suwarno (Jurnal Belantara, 2023)
Community needs are increasing day by day. Utilization of Non-Timber Forest Products (NTFPs) has started to become one of the focuses of community development.Â  If the local community understands the economic value and contribution of NTFP utilization, then the Halaban Village community will have the best potential and utilization of NTFPs. Remember the importance of forest resources for community income, then necessary to do a study related to the economic value and contribution of NTFPs. The purposes of research are to : (1) Calculate the economic value of non-timber forest products used by the Halaban village community, Lareh Sago Halaban District, 50 Cities Regency. (2) Analyze how the contribution of non-timber forest products to the income of the community in Halaban Village, Lareh Sago Halaban District, Lima Puluh Kota Regency. The data collection methods used in this research were observation, interview, questionnaire, and documentation. The results showed that the types of NTFPs that contributed to the Halaban village were rubber, cardamom, cinnamon, gambier, and areca nut. The total economic value of non-timber forest products (NTFPs) used by the Halaban Village community is Rp. 4,591,137,979,-/year. The total income obtained by the people of Halaban Village is Rp.7.304.337.979,-/year. The total economic value of NTFPs utilized by the community was Rp.7.304.337.979,-/year. NTFPs contribute 63% to community income.